+0

# Derivation help!

+5
342
6
+122

$$f'(x)=(x-2)/\sqrt{x}$$

How do I get the answer x+2/2xsqrtx ?

Namodesto  Dec 1, 2015

#4
+91450
+10

Ok  Namodesto

I have made some changes to the original post, let me know how you get on.

Why did I divide by x:

I used the quotient rule.  The denominator of the quotient rule is v^2

v=sqrt{x}

v^2 = x

Anyway let me know if youdo or if you don't understand :))

Melody  Dec 2, 2015
Sort:

#1
+91450
+15

The question is not written properly Namodesto

It should be like this

$$f(x)=\frac{x+2}{\sqrt{x}}\\ \mbox{Use quotient rule}\\ \boxed{If\;\;y=\frac{u(x)}{v(x)}\;\;then\;\;y'=\frac{vu'-uv'}{v^2} }\\ u=x+2 \quad v=x^{0.5}\\ u'=1 \qquad v'=0.5v^{-0.5}=\frac{1}{2\sqrt2}\\$$

$$(1)\qquad f'(x)=\frac{\sqrt{x}-\frac{1}{2\sqrt{x}}(x-2)}{x}\\ (2)\qquad f'(x)=\left[\sqrt{x}-\frac{1}{2\sqrt{x}}(x-2)\right] \div x\\ (3) \qquad f'(x)=\left[\frac{\sqrt{x}}{1}-\frac{(x-2)}{2\sqrt{x}}\right] \div x\\ (4) \qquad f'(x)=\left[\frac{2\sqrt{x}}{2\sqrt{x}}*\frac{\sqrt{x}}{1}-\frac{(x-2)}{2\sqrt{x}}\right] \div x\\ (5) \qquad f'(x)=\left[\frac{2\sqrt{x}}{2\sqrt{x}}*\frac{\sqrt{x}}{1}-\frac{(x-2)}{2\sqrt{x}}\right] \div x\\ (6) \qquad f'(x)=\left[\frac{2\sqrt{x}\sqrt{x}}{2\sqrt{x}*1}-\frac{(x-2)}{2\sqrt{x}}\right] \times \frac{1}{x}\\(7) \qquad f'(x)=\left[\frac{2x}{2\sqrt{x}}-\frac{(x-2)}{2\sqrt{x}}\right] \times \frac{1}{x}\\ (8) \qquad f'(x)=\frac{2x-(x-2)}{2\sqrt{x}}\times \frac{1}{x}\\ (9) \qquad f'(x)=\frac{2x-(x-2)}{2x\sqrt{x}}\\ (10) \qquad f'(x)=\frac{x+2}{2x\sqrt{x}}\\$$

I have added lines to help you understand and I have put line numbers so you can tell me which bit you do not understand.

So let me know how you get on :)

Melody  Dec 2, 2015
edited by Melody  Dec 2, 2015
edited by Melody  Dec 2, 2015
#2
+122
0

Hi Melody,

thank you so much for your help, however I still don't understand how you got 2x. And also why do you divide by x?

Namodesto  Dec 2, 2015
#4
+91450
+10

Ok  Namodesto

I have made some changes to the original post, let me know how you get on.

Why did I divide by x:

I used the quotient rule.  The denominator of the quotient rule is v^2

v=sqrt{x}

v^2 = x

Anyway let me know if youdo or if you don't understand :))

Melody  Dec 2, 2015
#5
+122
+5

Thank you Melody! I finally understand haha :)

Namodesto  Dec 2, 2015
#6
+91450
+5

That is great.  I am glad I could help :)

Melody  Dec 2, 2015

### 14 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details